Life cycle assessment produksi crude palm oil (CPO) (studi kasus: PT X Provinsi Bengkulu) - Reko Rinaldo; Suprihatin Suprihatin; Mohamad Yani (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
The development of oil palm plantations in Bengkulu Province has increased rapidly yearly. An increase also occurred in the CPO production sector. In 2021 the Bengkulu Province's CPO production rose to 30,052 tons of CPO from the total production in 2020 of 1,063,404 tons of CPO. PT X is a CPO production industry with a 30 tons/hour production capacity of FFB located in Bengkulu Province. PT X’s activities, from oil palm cultivation, fertilization and garden maintenance, industrial processing, waste treatment, and others, impact the environment and increase emissions. This research aims to evaluate the potential environmental impact of 1 tonne of CPO production. The method used is a life cycle assessment (LCA) with three impact categories: greenhouse gas (GHG) emission, acidification, and eutrophication. The boundary of the LCA study is cradle-to-gate, which includes the oil palm plantation subsystem and the industrial CPO production process subsystem. Based on the LCA results, the environmental impact of GHG, acidification, and eutrophication of 1 tonne of CPO production is 559.9 kg-CO2eq/tonne-CPO; 2.04 kg-SO2eq/tonne-CPO, and 0,96 kg-PO43-eq/tonne-CPO. GHG emission is the most significant impact resulting from the CPO production life cycle. Alternative recommendations for improvement to reduce the impact of replacing NPK fertilizer 12:12:17 with organic fertilizer EFB and using electricity from POME biogas (methane capture).